Moving from an L1 to an L2 Setting: Parents’ Motivation for Raising Children Bilingually - Restuningrum, Novi Rahayu (International Journal of Educational Best Practices, 2017)
This paper portrays changes in parents’ motivation for raising their children bilingually due to the change of domicile, from parents’ home country as the first language (L1) setting – which is a non English-speaking country – to Australia as their second language (L2) setting. Derived from a larger study done between 2011-2015, the paper describes how parents, who at the time of data collection resided in Australia, changed motivation for communicating with their children bilingually. Evolving from my personal experience, using an auto-ethnographic approach, and supported by data from two other research participants with similar experience, the paper presents a narrative on how parents’ sociolinguistic set-up is influenced by the geographic setting change. An early reason that became apparent why parents want their children to be able to communicate in two languages in the period prior to geographic movement from countries where English is a foreign language has changed after they live in Australia. Parents had been motivated to make their children bilingual when they are in the non-English-speaking contexts because they want their children to be able to fit in the globalised world communication. Meanwhile, their main reason for having bilingual children after they live in Australia is to maintain their heritage language and culture. This paper will enhance the discussion in the field of bilingualism, especially about parents’ motivation for children bilingualism and Family Language Policy (FLP), and will extend the discussion in other language-related field of research.